Animated Video to Improve Creative Thinking Skills in Plant Reproduction Material for Grade IV Elementary School - Made Debita Ismardani; Nice Maylani Asril; Ni Wayan Rati (Universitas Pendidikan Ganesha, 2025)
The mismatch between science learning objectives and the still-dominant conventional methods often hinders the stimulation of students’ imagination, preventing their creative thinking skills from developing optimally. This study aims to develop animated video media that is effective in enhancing the creative thinking abilities of fourth-grade students. The research employed the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were collected through questionnaires and tests, using questionnaire sheets and essay tests as instruments. The effectiveness of the media was measured using a one-group pretest–posttest design.The results show that the developed animated video media obtained a feasibility score of 95% from material experts and 96.19% from media experts. The practicality level, based on individual trials, was 90.95%, and 92.10% in small group trials, both falling into the “very practical” category. The Paired Sample T-Test results indicated a significance value of 0.000 < 0.05, suggesting a significant improvement in students’ creative thinking skills after using the media. In conclusion, the Canva-assisted animated video developed in this study is valid, practical, and effective for use in science learning. This media not only promotes the enhancement of creative thinking skills but also serves as an alternative learning strategy that encourages active student participation. Its implications highlight the potential for teachers to adopt this media as an innovative teaching resource aligned with technological advancements and the educational demands of the 21st century.